Heavy Metal Accumulation in Dominant Green Algae Living in a Habitat Under the Influence of Cu Mine Discharge Water - Kislioglu, Merve Sasmaz; Obek, Erdal; Konakci, Nevin; Sasmaz, Ahmet (Mdpi, 2025)
Algae absorb nutrients such as nitrogen (N) and phosphorus (P), as well as dissolved metal ions from polluted waters, and accumulate them in their tissues, thus contributing to the decontamination of water. This feature enables them to be used both as bioindicators of water pollution and in bioremediation applications aimed at the remediation of these waters. This study aims to define the dominant macroscopic green algae species developing in habitats affected by acidic leaks and currents from the copper mine operation site located in the Maden district of Elaz & imath;& gbreve; province (T & uuml;rkiye) and determine the extent to which these algal biomasses bioaccumulate selected metals (As, Cu, Cr, Hg, Cd, Ni, Pb, Zn) and contribute to water decontamination. For these purposes, metal (Fe, Cu, Zn, Mn, Cr, Pb and Cd) analyses were conducted on the algal biomasses collected from the abovementioned habitats and on water samples using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The dominant algal biomasses collected from the seepage water and Maden River habitats were identified as Ulothrix variabilis Kuetzing and Ulothrix tenuissima K & uuml;tzing, respectively. Heavy metal concentrations (mg/kg dry weight) in the biomasses of Ulothrix variabilis Kuetzing and Ulothrix tenuissima K & uuml;tzing species were determined as follows: Fe (11,094 mg/kg; 8.26 mg/kg) > Cu (6787 mg/kg; 180 mg/kg) > Zn (680 mg/kg; 283 mg/kg) > Mn (525 mg/kg; 13 mg/kg) > Co (838 mg/kg; 64 mg/kg) > Ni (472 mg/kg; 95 mg/kg)> Cr (164 mg/kg; 107 mg/kg) > Pb (83.6 mg/kg; 68.7 mg/kg) > Cd (1.48 mg/kg; 5.40 mg/kg), respectively. It was found that the affinity of both algal biomasses for the selected metal ions decreased in the order of Fe > Cu > Zn > Mn > Cr > Pb > Cd. Also, according to the calculated bioconcentration factor, it was shown that both algal biomasses were very good heavy metal accumulators. As a result, both algal biomasses can be used as effective biomonitoring agents and bioremediators for acidic and metal-laden polluted waters.
Keywords: Ulothrix sp.; mine drainage; heavy metals; algae; bioremediation; environment